Competence Based Education And Training For Social Economic Transformation - Dambudzo, Ignatius Isaac (Advances in Social Sciences Research Journal, 2018)
Concern has been expressed over the employability and inept demonstration of skills at work by TVET graduates. This has led to questions about the reasons for the negative outcomes. A combination of observations, discussions in comparative studies led to scrutiny of the training of TVET school leavers. The study sought to discover strategies that can be employed to enhance the quality of outcomes and employability of college leavers. This was a qualitative study in which data collection from 35 trainees was done using observation reports of teacher trainees. Results have shown that employment of CBET may enhance skills development due to the element of industrial attachment where trainees will work under experienced and knowledgeable mentors as trainee teachers do. The model used for teacher training was recommended for other TVET sectors to enable the participation of industry in the training of future personnel within their environment. Trainees expressed satisfaction with the use of CBET because it exposed them to both natural working environment and mentoring by experienced and knowledgeable experts. The training arrangement enhanced their skills and knowledge in preparation for the world of work on completion. CBET was therefore an alternative training method which can be extended to industry from teaching.